Impact Of Compensation And Work Discipline On Employee Performance With Work Motivation As Intervening Variable (Case Studies Of LAZIS Muhammadiyah) - Sabar Waluyo; Amir Amir; Suyoto Suyoto; Ani Kusbandiyah (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The study aims to study the impact of compensation, work discipline, and motivation on employee performance, with motivation as an intervening variable. The study analyzed data from 105 respondents using quantitative approaches and Partial Least Squares Structural Equation Modeling (PLS-SEM). In addition, although compensation has a significant impact on work motivation, work discipline also strongly affects work motivations. Work motivation has been shown to mediate the relationship between compensation and employee performance. These findings suggest that in addition to competitive compensation, improving employee discipline and motivation can be an effective strategy for improving performance. The results of this research can serve as a benchmark for managers to formulate more effective compensation policies and develop human resources.